Pengaruh Sarapan Sehat terhadap Kondisi Fisik Anak Usia Dini - Wahyuningsih, Melly Sri; Jannah, A.Miftahul; Pratiwi, A.Nurul; Khaerunnisa, Khaerunnisa; Munawir, A. Nidha Eka Restuti (Jurnal Pendidikan Tambusai, 2026)
Early Childhood Education (PAUD) requires healthy breakfast as essential nutrition to support stamina and learning readiness, yet 65 percent breakfast skipping prevalence in Indonesia causes fatigue and motor impairments. This study aims to analyze the effect of healthy breakfast on PAUD children's physical condition. Literature review with descriptive qualitative approach employed, targeting all tertiary articles from 2015-2025 on Google Scholar and Scopus, sampling 20 selected articles focused on morning nutrition in early childhood. Secondary documents served as instruments, analyzed via data reduction, display, and verification to confirm breakfast influence patterns. Findings reveal children consuming balanced breakfast exhibit better stamina, reduced fatigue, and lower obesity risk through stable energy and optimal micronutrients mechanisms. Conclusion recommends synergy among parents, PAUD institutions, and policies to foster sustainable breakfast habits for holistic child development optimization